A new species of dwarf gecko in the genus Lygodactylus (squamata: Gekkonidae) from central Kenya - Malonza, Patrick K.; Granthon, Carolina; Williams, Dean A. (Zootaxa, 2016)
A new species of Lygodactylus gecko (L. wojnowskii sp. nov.) is described from the vicinity of Chogoria Town on the eastern lower slopes of Mt. Kenya in central Kenya. A phylogeny based on mitochondrial and nuclear DNA shows that the proposed new taxon is distinct within the Lygodactylus picturatus group and is the sister lineage to L. mombasicus and L. kimhowelli. It is morphologically very similar to both L. mombasicus and L. keniensis but its dorsal coloration and pattern is different. Its dorsum is grey with dark stripes while its head has black and white stripes that form a Y-shaped mark. While the male throat pattern is similar to that of L. mombasicus, that of the female is like that of females and some males of Lygodactylus keniensis. Lygodactylus wojnowskii sp. nov. has a higher number of post-postmental scales (6) than do its close relatives (5). The new species is distributed on the lower slopes of mid-altitude areas on eastern Mt. Kenya, but it may occur in other areas at similar elevations in central Kenya. It is associated with short, scattered trees within agricultural areas. It has not yet been recorded within the protected Chogoria forest block of Mt. Kenya forest. It is likely present in Mwea National Reserve as it occurs in nearby areas.